Burnout and retaliatory attitudes: a study of young Brazilian workers - Kely César Martins de Paiva; Thais Pinto da Rocha Torres; Jefferson Rodrigues Pereira; Victor Natanael Schwetter Silveira (Tourism & Management Studies)
This study sought to analyse the relationship between burnout variables and retaliatory attitudes in young workers. A descriptive case study was conducted based on a quantitative approach, focusing on young people in two Brazilian state capitals: Curitiba in Parana, and Porto Alegre in Rio Grande do Sul. A three-part questionnaire was administered, and the final sample contained 526 valid survey forms. The data analysis used exploratory factor analysis and structural equation modelling. Emotional exhaustion is related to individuals’ feelings of indignation at perceived injustices and perceptions of justice. Low personal accomplishment is negatively related to judgment of retaliation. The latter finding contributes significantly to the literature, which has few articles linking these two constructs. Organisations can use the results to improve how they deal with younger workers and their specific burnout and retaliatory attitudes, thereby improving quality of life for not only all workers on the job but also young people specifically